2022
DOI: 10.1016/j.omto.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Dual-targeting vaccine of FGL1/CAIX exhibits potent anti-tumor activity by activating DC-mediated multi-functional CD8 T cell immunity

Abstract: Tumor DNA vaccine as an effective therapeutic approach can induce systemic immunity against malignant tumors, but its therapeutic effect is still not satisfactory in advanced renal cancer. Herein, a novel DNA vaccine containing dual antigens of fibrinogen-like protein 1 (FGL1) and carbonic anhydrase IX (CAIX) was developed and intramuscularly delivered by PLGA/PEI nanoparticles for renal cancer therapy. Compared with PLGA/PEI-pCAIX immunization, PLGA/PEI-pFGL1/pCAIX co-immunization significantly inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Our previous study has demonstrated that PLGA/PEI-mediated DNA delivery system is able to promote DNA vaccine to penetrate the biological barriers and transfer the plasmid into the nucleus of the target cell to express it stably. 31 In this study, our result also demonstrated that PLGA/PEI-HMGB1/GPC3 vaccine could be efficiently expressed in vitro and in vivo . The immunogenicity and therapy effect of the PLGA/PEI-HMGB1/GPC3 vaccine was evaluated in the HCC model.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our previous study has demonstrated that PLGA/PEI-mediated DNA delivery system is able to promote DNA vaccine to penetrate the biological barriers and transfer the plasmid into the nucleus of the target cell to express it stably. 31 In this study, our result also demonstrated that PLGA/PEI-HMGB1/GPC3 vaccine could be efficiently expressed in vitro and in vivo . The immunogenicity and therapy effect of the PLGA/PEI-HMGB1/GPC3 vaccine was evaluated in the HCC model.…”
Section: Introductionsupporting
confidence: 66%
“… 41 PLGA/PEI-mediated DNA vaccine could also shield the delivered antigens from degradation to further improve their uptake into DCs and induce the maturity of DCs. 31 The results of the present study showed that PLGA/PEI-HMGB1/GPC3 vaccine can significantly promote the ratio of CD8 + DCs and CD103 + DCs, thus indicating that the nanoparticle can sufficiently bolster the magnitude of the CTL effect via DCs-mediated anti-tumor response. In addition, the design of a vaccine strategy targeting DCs might offer great promise for enhancing the immune response against the tumor.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…An increasing number of studies have strongly suggested that FGL1 is highly expressed in various tumor tissues and may serve as a pan-cancer prognostic biomarker [ 8 , 12 , 17 ]. Recent studies have shown that targeting FGL1 may serve as a new strategy for tumor immunotherapy [ 18 , [32] , [33] , [34] , [35] ]. However, the molecular mechanisms of FGL1 in different cancer types remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies target the innate immunity that aims to present tumor antigens to cytotoxic T cells to stimulate anti-tumor responses. In this issue, Chai et al 8 developed a novel dual-targeting DNA-based vaccine, specifically for fibrinogen like 1 and carbonic anhydrase IX antigens for renal cell cancers, by targeting dendritic cell subsets to generate multi-functional CD8 + T cell responses against metastasis. Yeo et al 9 reviewed the challenges facing immunotherapy for treating patients with pancreatic cancer that is notoriously resistant to most therapeutic interventions, including cell-based therapies.…”
Section: Beyond the Engineered T Cellmentioning
confidence: 99%